2013
DOI: 10.4236/health.2013.51004
|View full text |Cite
|
Sign up to set email alerts
|

Overweight, obesity and associated factors among secondary school students in a northern city of Vietnam in 2011

Abstract: Overweight and obesity is an emerging public health problem among school-aged children in Bac Giang city in the Northen part of Vietnam recently. This study aims to identify overweight-obesity prevalence of secondary school children in this city and it’s associated factors. The study was a nested case control in a cross Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…Similarly, the prevalence of overweight, for children aged five to sixteen years, was 6.6% in the year 2005 in India [3] ; Ethiopia reported a prevalence of 3.3% in school-aged children [4] . Lastly, in Vietnam there was a prevalence of 6.7% and 2.0% of overweight and obesity, respectively, among children aged eleven to fourteen years old [5] .…”
Section: Introductionmentioning
confidence: 92%
“…Similarly, the prevalence of overweight, for children aged five to sixteen years, was 6.6% in the year 2005 in India [3] ; Ethiopia reported a prevalence of 3.3% in school-aged children [4] . Lastly, in Vietnam there was a prevalence of 6.7% and 2.0% of overweight and obesity, respectively, among children aged eleven to fourteen years old [5] .…”
Section: Introductionmentioning
confidence: 92%
“…Although most of the earliest studies which surveyed the prevalence of overweight and obesity among Vietnamese children was conducted in Ho Chi Minh City-a metropolitan city of Vietnam, numerous papers indicate different findings [12][13][14][15][16][17][18][19][20]. The details describing the various findings of previous studies is shown in the S2 Table. During 2007-2010, it was evident that there was a low proportion of overweight (around 10%) and obese (less than 2%) children according to IOTF reference [13,16] and WHO Z-score [12] were reported while malnutrition of Vietnamese children also remained a significant issues at that time [12].…”
Section: Prevalence Of Overweight and Obesitymentioning
confidence: 99%
“…However, this report only provides information using the WHO Z-score criteria and does not provide information in regards to the sampling method [12]. There have been some studies which examine the obesity prevalence among Vietnamese children and adolescents currently [13][14][15][16][17][18][19][20]. However, a major limitation of these studies is that the investigators used either WHO Z-score or IOTF reference for calculating and surveyed small districts of Vietnamese metropolis (mostly in Ho Chi Minh city) [13,14,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations